Uncertainty and the Employment Dynamics of Small and Large Businesses - Ghosal, Vivek (IMF Working Papers; Working Paper, 2015)
We examine the impact of uncertainty on employment dynamics. Alternative measures of uncertainty are constructed based on the survey of professional forecasters, and regressionbased forecasting models for GDP growth, inflation, S and P500 stock price index, and fuel prices. Our results indicate that greater uncertainty has a negative impact on growth of employment, and the effects are primarily felt by the relatively smaller businesses; the impact on large businesses are generally non-existent or weaker. Our results suggest that to truly understand the effects of uncertainty on employment dynamics, we need to focus on the relatively smaller and entrepreneurial businesses. We discuss implications for the framing of economic policy.